2017
DOI: 10.1002/ijc.30575
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt lymphoma expresses oncofetal chondroitin sulfate without being a reservoir for placental malaria sequestration

Abstract: Burkitt lymphoma (BL) is a malignant disease, which is frequently found in areas with holoendemic Plasmodium falciparum malaria. We have previously found that the VAR2CSA protein is present on malaria-infected erythrocytes and facilitates a highly specific binding to the placenta. OfCS is absent from other non-malignant tissues and thus VAR2CSA generally facilitates parasite sequestration and accumulation in pregnant women. In this study, we show that the specific receptor for VAR2CSA, the oncofetal chondroiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Counterintuitively, compared to controls, serum from eBL cases in both Ghana and Uganda showed lower breadth and intensity of IgG reactivity to Pf EMP1 CIDR domains. This finding mirrors our previous observation of decreased IgG reactivity to VAR2CSA in a different set of samples from the Ghana study [20]. The lower breadth and intensity of IgG reactivity to Pf EMP1-derived antigens affected all Pf EMP1 functional domain types in Ghana and Uganda; thus, the reduced IgG reactivity is unrelated to Pf EMP1 functional phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…Counterintuitively, compared to controls, serum from eBL cases in both Ghana and Uganda showed lower breadth and intensity of IgG reactivity to Pf EMP1 CIDR domains. This finding mirrors our previous observation of decreased IgG reactivity to VAR2CSA in a different set of samples from the Ghana study [20]. The lower breadth and intensity of IgG reactivity to Pf EMP1-derived antigens affected all Pf EMP1 functional domain types in Ghana and Uganda; thus, the reduced IgG reactivity is unrelated to Pf EMP1 functional phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…When considering previously published data showing that ofCS is presented by nearly all cancer cells of epithelial, mesenchymal, and hematopoietic origin, the use of rVAR2 staining reagent for CTC detection would be beneficial over traditional single-surface markers [25,27,33,34]. Here, we show that captured glioma CTCs can be identified by an rVAR2 stain.…”
Section: Discussionmentioning
confidence: 69%
“…We have previously shown that the rVAR2 protein interacts with ofCS present on cancer cell lines representing almost all known cancers [25,33,34]. We tested rVAR2 binding to a panel of cell lines, including low-grade (WHO grade II) diffuse glioma (Res259) as well as high-grade (WHO grade IV) GBM (U87mg, KNS-42, and U118mg), to test for the presence of ofCS in glioma.…”
Section: Resultsmentioning
confidence: 99%
“…Children with immunity to malaria have a lower risk of death from severe malaria [ 16 , 18 ], but they are exposed to chronic falciparum parasitemia and increased activity by splenic macrophages to clear parasites [ 17 ]. We suggest that this increased falciparum antigenic load to the spleen is a risk factor for eBL [ 45 ] in children in malaria endemic regions. We further infer that it is not high-risk falciparum variants (as is the case for severe malaria), but the multiplicity of diverse variants the children are exposed to that are the risk factor for eBL [ 46 ].…”
Section: Discussionmentioning
confidence: 99%